(untitled) (Bangladesh Journal of Agriculture, 2023)
A study was conducted to observe the soil properties under naturally occurring saline soil conditions in Bagerhat and Pirojpur. Soil samples at 0-20 cm depth were collected from Bagerhat sadar and Khachua upazila under Bagerhat district and Projpur sadar and Nazirpur upazila under Projpur district. Observations were made on soil pH, organic matter, cation exchange capacity (CEC), electrical conductivity (EC), exchangeable sodium percentage (ESP), total N, available P, S and exchangeable K, Ca, Na and Mg contents. Result indicates that pH value ranged from 6.70 to 7.40 and 6.60 to 7.79, organic matter 1.75 to 3.61% and 1.57 to 2.90 %, total N 0.11 to 0.18% and 0.08 to 0.97 %, available P 7.40 to 39.18 mg/kg and 2.92 to 23.40 mg/kg and 0.20 to 1.04%, available S 15.53 to 66.82 mg/kg and 3.50 to 35.53 mg/kg in Bagerhat and Pirojpur districts, respectively. In Bagerhat and Pirojpur districts, EC varied from 2.84 to 7.10 ds/m and 1.16 to 4.90 ds/m, CEC 9.77 to 36.35 and 10.34 to 48.70 meq100g-1 soils, exchangeable Na 0.62 to 2.80 meq100g-1 soil and 0.75 to 2.11 meq100g-1 soil, exchangeable K 4.20 to 22.68 meq100g-1soil and 3.64 to 41.04 meq100g-1 soil, exchangeable Ca 0.84 to 8.37 meq100g-1 and 0.80 to 17.82 meq100g-1, exchangeable Mg 0.13 to 0.60 meq100g-1 soil 0.17 to 0.38 meq100g-1 soil and ESP 4.36 to 11.72 and 3.12 to 7.34, respectively. In Bagerhat, a positive significant correlation of CEC was found with total N, K, EC, Na, K, Ca and Mg contents. In Pirojpur, a negative significant correlation of CEC was found with OM, S and Na contents. The paired shows that S, EC, CEC, K, Ca and ESP will significant between the two locations. These results would be useful for predicting crop production and varietal response to soil nutrient conditions and developing fertilizer management in the coastal areas of Bangladesh. Bangladesh J. Agri. 2022, 47(2): 143-160